MORPHOLOGICAL ANALYSIS ON THE WORD FORMATION PROCESSES FOUND IN THE TERMS OF MICROSOFT POWERPOINT 2010 PROGRAM - EFENDI, NUR (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Morphology, Word Formation, Microsoft PowerPoint 2010 program. In the word formation study, some words from the foreign languages have probabilities to become the part of English vocabularies.This study aims atinvestigating the word formation processes found in the terms of MicrosoftPowerPoint 2010 Program and the kinds of word formation processes which ismostly used in the terms of Microsoft PowerPoint 2010 Program.In this study, the writer conducted a qualitative research, because thisstudy concerns with how words are processed, and not dealing with number. Thetype of research was document analysis. The source of data in this study wasMicrosoft PowerPoint 2010 program. In conducting this study, the writer usedYule’s theory and supported by Akmajian’s about the kinds of word formationprocesses.Based on the result of the study, the writer found six kinds of wordformation processes in the terms of Microsoft PowerPoint 2010 program, namely: compounding, borrowing, blending, multiple processes, derivational affix, and inflectional affix. The type of word formation process which is mostly used in the terms of Microsoft PowerPoint 2010 Program is inflectional affix.There are many terms found in Microsoft PowerPoint 2010 program that can be constructed through word formation processes especially inflectional affix process.This study is expected to be useful for English Department students. Moreover, the researcher hopes the future researchers who are interested inmorphology, especially word formation processes, may use new completereferences and different object of study. The researcher also hopes this thesis can be a reference or information for English Department students who are interested in conducting a study concerning word formation processes of computer program. Moreover, English Department students who are interested in analyzing the word formation processes or other elements of morphology can use the newest theories from the expert of morphology.